If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (x + 7) = 12 Reorder the terms: X + (7 + x) = 12 Remove parenthesis around (7 + x) X + 7 + x = 12 Reorder the terms: 7 + X + x = 12 Solving 7 + X + x = 12 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + X + -7 + x = 12 + -7 Reorder the terms: 7 + -7 + X + x = 12 + -7 Combine like terms: 7 + -7 = 0 0 + X + x = 12 + -7 X + x = 12 + -7 Combine like terms: 12 + -7 = 5 X + x = 5 Add '-1x' to each side of the equation. X + x + -1x = 5 + -1x Combine like terms: x + -1x = 0 X + 0 = 5 + -1x X = 5 + -1x Simplifying X = 5 + -1x
| 14x-12=36 | | |2x+4|=0 | | -7x+17=9-10y | | -2(x-2)+x=16 | | 150-5w=30+10w | | 3x(5+3x)=10 | | 4t^2+12t+8=0 | | 1-5(7k+4)=-299 | | -2w-5w=4 | | g(w)=-2w^2-8w+1 | | 7x+8=-16+24y | | 5a+eb=7 | | 5x+15=25x+5 | | 35x=85x-5 | | -2x+x=16 | | 2x+9y=48 | | 18y+9=3x+6 | | 17+3=14 | | 3x^2-5x=50 | | 2x-3x+5x=32 | | 4k+14=2 | | (2/3)n=4(n-2) | | 4(4x+1)=684 | | 3(x+1)+1+2x=2(2x+2)+c | | 10+4x=16x+8 | | 4x-y=-6 | | 5p=6.25-5r | | 5(n+2)=3(n-4) | | 7x^2+24=y-6x*(2-3x^2) | | p=3x-(100+2) | | 5(x+2)=4(3x-2) | | 7c+2-6c=-28+6 |